THU0640 EARLY RETIREMENT ATTRIBUTED TO RHEUMATOID ARTHRITIS AND ITS PREDICTORS IN PORTUGAL. (June 2019) - Luis, Mariana; Cunha, Ana Rita; Assunção, Helena; Prata, Ana Rita; Brites, Luisa; Costa, Flavio; Freitas, João Dinis de; Silva, Stephanie; Barcelos, Anabela; Duarte, Catia; Da Silva, José Antonio P.
Abstract : Background: Work disability is a common consequence of Rheumatoid Arthritis (RA) with economic implications for both the patient and society. Scarce information is available on work and disease-related factors associated with early retirement in Portugal. Objectives: To evaluate the rate of early retirement due to RA. Secondary aim consists in the identification of its main predictors, both work and disease-related. Methods: Retrospective cohort study involving two national rheumatology centers, including patients with RA according the ACR/EULAR 2010 or the 1987 ACR Classification Criteria for RA. Patients retired prior to RA diagnosis, never-employed or with missing information on current work status were excluded. Type of work was independently classified as non-manual/manual/heavy manual by two authors based on patient's occupation with excellent inter-agreement (Cohen's kappa coefficient 0.91). Retirement due to RA versus retirement for other reasons were compared using T-test and Chi-2 test as adequate. Variables with p<0.05 in univariate analysis and other potential predictors selected on clinical and epidemiological grounds were included in multivariable binary logistic regresssion. Results: 492 patients were included (80.3% female, aged 60.9 ±13.1 years-old, mean disease duration 15.9 ±10.5 years). Until the present time, 45.1% (n=222) of the patients retired, this being due to RA in 59.5% of the cases. Early retirement due to RA translated into 6.5 years of active work lost, compared to retirement due to other causes. Patients who retired due to RA are more likely to be younger at diagnosis (49.6 ± 9.0 vs. 56.1 ± 8.6 years-old; p<0.01), female (82.6% vs. 68.9%, p<0.01), have longer disease duration (23.2 ± 10.7 vs. 18.3 ± 9.9 years, p<0.01) and lower educational level (4.5 ± 2.3 vs. 6.0 ± 4.1 school years, p<0.01). In the multivariate analysis, disease-related predictors for early retirement were: disease duration (OR: 1.11; 95% CI 1.08-1.13/year), erosive disease (OR: 4.45 95% CI 2.37-8.35) and the need for biologic therapy switching (OR:1.37; 95%CI 1.02-1.83). Work-related predictors were: educational level (OR: 0.75; 95%CI 0.68-0.81/year) and heavy manual type of work (OR: 1.62; 95%CI 1.16-2.26). Conclusion: Early retirement is still common among patients with RA: 60% in this cohort. The main reasons for early retirement are associated with the disease itself, but work-related factors also play a relevant role. References: [1] P. A. Laires, M. Gouveia. Association of rheumatic diseases with early exit from paid employment in Portugal. Rheumatol Int (2014) 34:491–502. [2] K. Puolakka, H. Kautiainen, T. Mottonen, P. Hannonen, et al. Predictors of productivity loss in early rheumatoid arthritis: a 5 year follow up study. Ann Rheum Dis2005;64:130–133. [3] D. Lacaille, S. Sheps, J. J. Spinelli, A. Chalmers, J. M. Escaile. Identification of modifiable work-related factors that influence the risk of work disability in rheumatoid arthritis. Arthritis Rheum. 2004Oct15;51(5):843-52. Disclosure of Interests: None declared